Long-Term Care Health Care Aides' Perceptions of Decision-Making Processes in Transferring Residents to Acute Care Services. (August 2020) - Tate, Kaitlyn; Spiers, Jude; El-Bialy, Rowan; Cummings, Greta
Most transfers of long-term care (LTC) facility residents to the emergency department (ED) via 911 calls are necessary. Avoidable transfers can have adverse effects including increased confusion and dehydration. Around 20% of transfers are perceived to be avoidable or unnecessary, yet decision making around transfers is complex and poorly understood. Using a qualitative-focused ethnographic approach, we examined 20 health care aides' (HCAs) perceptions of decision processes leading to transfer using experiential interview data. Inductive analysis throughout iterative data collection and analysis illuminated how HCAs' familiarity with residents make them vital in initiating care processes. Hierarchical reporting structures influenced HCAs' perceptions of nurse responsiveness to their concerns about resident condition, which influenced communications related to transfers. Communication processes in LTC facilities and the value placed on HCA concerns are inconsistent. There is an urgent need to improve conceptualization of HCA roles and communication structures in LTCs.